2014
DOI: 10.1007/s00167-014-3111-5
|View full text |Cite
|
Sign up to set email alerts
|

Return to sports, recreational activity and patient-reported outcomes after lateral unicompartmental knee arthroplasty

Abstract: Retrospective case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 35 publications
5
76
1
2
Order By: Relevance
“…High and regular athletic activity leads to an increase in stress on the implant-bone interface which may potentially lead to an acceleration of wear and therefore to higher revision rates in young and active patients after total joint arthroplasty [32,[42][43][44]. Due to the mobile meniscal bearing in OUKA, fully congruent contact between the components is ensured throughout flexion and extension leading to compression forces instead of shear forces with low wear rates at long-term followup [32,45,46].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…High and regular athletic activity leads to an increase in stress on the implant-bone interface which may potentially lead to an acceleration of wear and therefore to higher revision rates in young and active patients after total joint arthroplasty [32,[42][43][44]. Due to the mobile meniscal bearing in OUKA, fully congruent contact between the components is ensured throughout flexion and extension leading to compression forces instead of shear forces with low wear rates at long-term followup [32,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…have reported the physical activity after unicompartmental knee arthroplasty [27,[29][30][31][32]. In a series of 83 patients, Naal et al reported a return to activity rate of 95% 18 months after the implantation of the fixed bearing Preservation prosthesis [30]; Fisher et al demonstrated a rate of 93% 18 months after medial Oxford unicompartmental knee arthroplasty (OUKA) in a series of 76 patients [29]; Hopper et al reported a return to activity rate of 96.7% in a series of 37 patients 22 months after OUKA [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations